Toll-like receptors 2, 4, and 9 modulate promoting effect of COPD-like airway inflammation on K-ras-driven lung cancer through activation of the MyD88/NF-ĸB pathway in the airway epithelium - Velasco, Walter V.; Khosravi, Nasim; Castro-Pando, Susana; Torres-Garza, Nelly; Grimaldo, Maria T.; Krishna, Avantika; Clowers, Michael J.; Umer, Misha; Tariq Amir, Sabah; Del Bosque, Diana; Daliri, Soudabeh; De La Garza, Maria Miguelina; et al. (Frontiers in Immunology, 2023)
Toll-like receptors (TLRs) are an extensive group of proteins involved in host defense processes that express themselves upon the increased production of endogenous damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs) due to the constant contact that airway epithelium may have with pathogenic foreign antigens. We have previously shown that COPD-like airway inflammation induced by exposure to an aerosolized lysate of nontypeable Haemophilus influenzae (NTHi) promotes tumorigenesis in a K-ras mutant mouse model of lung cancer, CCSPCre/LSL-K-rasG12D (CC-LR) mouse. In the present study, we have dissected the role of TLRs in this process by knocking out TLR2, 4, and 9 and analyzing how these deletions affect the promoting effect of COPD-like airway inflammation of K-ras-driven lung adenocarcinoma. We found that knockout of TLR 2, 4, or 9 results in a lower tumor burden, reduced angiogenesis, and tumor cell proliferation, accompanied by increased tumor cell apoptosis and reprogramming of the tumor microenvironment to one that is antitumorigenic. Additionally, knocking out of downstream signaling pathways, MyD88/NF-ĸB in the airway epithelial cells further recapitulated this initial finding. Our study expands the current knowledge of the roles that TLR signaling plays in lung cancer, which we hope, can pave the way for more reliable and efficacious prevention and treatment modalities for lung cancer.